2017
DOI: 10.1002/anie.201704908
|View full text |Cite
|
Sign up to set email alerts
|

Geometry‐Retentive C‐Alkenylation of Lithiated α‐Aminonitriles: Quaternary α‐Alkenyl Amino Acids and Hydantoins

Abstract: α-Amino nitriles tethered to alkenes through a urea linkage undergo intramolecular C-alkenylation on treatment with base by attack of the lithionitrile derivatives on the N'-alkenyl group. A geometry-retentive alkene shift affords stereospecifically the E or Z isomer of the 5-alkenyl-4-iminohydantoin products from the corresponding starting E- or Z-N'-alkenyl urea, each of which may be formed from the same N-allyl precursor by stereodivergent alkene isomerization. The reaction, formally a nucleophilic substitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…[20][21][22][23][24] Given this conformational constraint, nitrile-stabilised carbanions 25 will attack an unactivated C-N bond, directed by the conformational preference of a urea function (Scheme 1a), yielding iminohydantoin and hydantoin products. [26][27][28] We now show that the use of such anions in a ringexpansion reaction of nitrogen heterocycles leads to a two-carbon insertion into an aromatic C-N bond, with tandem formation of a bridging (imino)hydantoin ring (Scheme 1b).…”
Section: Introductionmentioning
confidence: 87%
“…[20][21][22][23][24] Given this conformational constraint, nitrile-stabilised carbanions 25 will attack an unactivated C-N bond, directed by the conformational preference of a urea function (Scheme 1a), yielding iminohydantoin and hydantoin products. [26][27][28] We now show that the use of such anions in a ringexpansion reaction of nitrogen heterocycles leads to a two-carbon insertion into an aromatic C-N bond, with tandem formation of a bridging (imino)hydantoin ring (Scheme 1b).…”
Section: Introductionmentioning
confidence: 87%
“…We recently reported a direct and general synthesis of enantiomerically enriched α‐arylated quaternary amino acids by combining the electronically versatile intramolecular S N Ar chemistry characteristic of N’ ‐aryl ureas with Seebach's ‘self‐regeneration of stereocenters’ methodology (Scheme a) . We have found that N ′‐alkenyl groups likewise migrate from N′ to C within anionic derivatives of ureas, and we now report a practical method for the α‐functionalization of amino acids with alkenyl substituents (Scheme b) in which both the absolute configuration of the stereogenic center and geometric configuration of the double bond are controlled.…”
Section: Methodsmentioning
confidence: 98%
“…The N’ ‐allyl ureas 2 were isomerized to the E ‐alkenyl ureas E ‐ 3 with a Ru catalyst and to Z ‐alkenyl ureas Z ‐ 3 by γ reprotonation of the Z ‐configured allyllithium derivative of 2 with a bulky proton source (Scheme ) . These methods allowed the stereodivergent formation of four stereoisomers of 3 a as starting materials for alkenyl migration having either 2 R or 2 S configuration at the tert ‐butyl‐bearing center and either E or Z double bond geometry.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[8] These are immediate precursors of both hydantoins 4 and amino acids 5, which may be revealed by hydrolysis. [9] The method would furthermore be independent of the configuration of the amino acid moiety, making it particularly applicable to non-proteinogenic amino acids such as phenylglycines. In order to explore this proposal with an amino-acid derivative bearing 'unnatural' substituents, a trial urea 6a was made as a 1:1 mixture of diastereoisomers from optically pure (R)-1-(4methoxyphenyl)ethylamine in a 3 step sequence involving a Strecker reaction, [10] N-phosgenation of the resulting aminonitrile, and urea coupling with N-methylaniline.…”
Section: Lithiation Of N'-arylureas Derived From Amino Nitriles Incormentioning
confidence: 99%